The Influence Of Workload And Working Environment On Employee Performance At PT. Megatama Abadi Irs Serang City - Prawesty, Dias Ayu; Syukri, Ahmad (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2025)
This study aims to analyze the effect of workload and work environment on employee performance at PT Megatama Abadi IRS (Industrial Rotating Service) using an associative quantitative approach. The research sample consists of 60 employees selected using a saturated sampling technique. Data analysis was conducted through descriptive statistics, validity tests, reliability tests, classical assumption tests, as well as simple and multiple linear regression analysis. The results indicate that workload and work environment simultaneously have a positive and significant impact on employee performance, with an F-calculated value of 37.559 greater than the F-table value of 4.01 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 56.9% suggests that workload and work environment variables contribute to employee performance, while the remaining 43.1% is influenced by other factors.